Influence of oxygen exposure on fermentation process and sensory qualities of Sichuan pickle (paocai). Issue 66 (26th November 2019) - Rao, Yu; Qian, Yang; Tao, Yufei; She, Xiao; Li, Yalin; Che, Zhenming; Li, Hehe; Liu, Lei
Abstract : The physicochemical and microbial changes, volatile profile, texture and appearance were investigated in three groups of Sichuan pickles differing in oxygen exposure during a 64 day fermentation process. Abstract : The physicochemical and microbial changes, volatile profile, texture and appearance were investigated in three groups of Sichuan pickles differing in oxygen exposure during a 64 day fermentation process. At the beginning, all the Sichuan pickles displayed similar sensory and fermentation characteristics regarding lactic acid bacteria domination, sugar utilization, and lactate accumulation. Soon afterwards, continued exposure allowed premature pellicle formation and typical aerobic deterioration of Sichuan pickle, accompanied by texture destruction and an odorous stench characterized by arenes and aldehydes on the 32 nd day. Meanwhile, the facultative anaerobes including Lactobacillus (90 ± 2%), Pediococcus (4.7 ± 0.3%) and Lactococcus (1.2 ± 0.8%) were the dominant genera and probably associated with acetic acid production and arene enrichment under oxygen exposure conditions on the 32 nd day. Until the 48 th day, intermittent oxygen exposure resulted in pellicle formation and an unpleasant flavor characterized by ketones, esters and S-methyl thioacetate. In comparison, Sichuan pickle without oxygen exposure always maintained a relatively favorable fragrant scent and texture. Besides Lactobacillus, anaerobic genera were the main bacteria in Sichuan pickle under closed conditions and accounted for 50 ± 9% of the total bacteria on the 32 nd day. The study indicated the microbial and chemical characteristics of Sichuan pickles during practical production and provided a theoretical guidance for the industrial production of Sichuan pickle.